2020
DOI: 10.1177/0146167220922643
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of Islamophobia: A Test of a Tripartite View in Five Countries

Abstract: This article provides an examination of the structure of Islamophobia across cultures. Our novel measure—the Tripartite Islamophobia Scale (TIS)—embeds three theoretically and statistically grounded subcomponents of Islamophobia: anti-Muslim prejudice, anti-Islamic sentiment, and conspiracy beliefs. Across six samples (i.e., India, Poland, Germany, France, and the United States), preregistered analyses corroborated that these three subcomponents are statistically distinct. Measurement invariance analyses indic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 55 publications
2
21
0
Order By: Relevance
“…The literature offers a few potential explanations. First, conspiracy stereotypes can be viewed as a subcomponent of various forms of prejudice (e.g., antisemitism [11,30]; islamophobia, [19]), and a core aspect of prejudice is to deny the existence of discrimination [40]. Thus, a first mechanism through which conspiracy believers may come to downplay the powerlessness of the outgroup may be simply to deny it.…”
Section: Attribution Of Power As a Necessary Property Of Conspiracy T...mentioning
confidence: 99%
See 1 more Smart Citation
“…The literature offers a few potential explanations. First, conspiracy stereotypes can be viewed as a subcomponent of various forms of prejudice (e.g., antisemitism [11,30]; islamophobia, [19]), and a core aspect of prejudice is to deny the existence of discrimination [40]. Thus, a first mechanism through which conspiracy believers may come to downplay the powerlessness of the outgroup may be simply to deny it.…”
Section: Attribution Of Power As a Necessary Property Of Conspiracy T...mentioning
confidence: 99%
“…For instance, as highlighted earlier, proponents of the great replacement conspiracy theory consider that the elites (i.e., the media, the government, intellectuals) are involved in the conspiracy [32]. In this regard, it is interesting that in research examining belief in conspiracy theories targeting Muslims, some measures include the involvement of authorities [38,41], while others do not [18,19]. Moreover, Muslim immigrants may be perceived as benefitting from the support of wealthy Muslim countries (e.g., Arab Emirates), or powerful Muslim organizations (e.g., the Muslim Brotherhood).…”
Section: Attribution Of Power As a Necessary Property Of Conspiracy T...mentioning
confidence: 99%
“…Muslims experience greater resistance than other religious outgroups due to Islamophobia being currently more socially acceptable in receiving Western societies (Creighton & Jamal, 2015; Uenal et al., 2020). This tendency was partly confirmed since we found that diversity threat was more negatively associated with support for Muslims’ religious rights than with support for religious minority rights in general in Australia and Finland.…”
Section: Discussionmentioning
confidence: 99%
“…Social identity motives [1][2][3]28], more than cognitive biases or personality factors as such, may become central to this next stage of the "spiritual journey". Social identity [i.e., 29] is indeed related to CTs that target hated outgroups [28, [30][31][32] or minorities [20,33].…”
Section: Engagementmentioning
confidence: 99%